The art of managing professional services : insights from leaders of the world's top firms - Broderick, Maureen, 1949- (Prentice Hall, 2011)
Today, millions of people work at over one million professional service firms generating over $2 trillion in revenue annually. These firms face unique issues that are not fully understood by management thinkers and consultants. Making matters more complex is that many of these firms stand at a crossroads, searching for new strategies and practices to succeed in a radically new economy. In The Art of Managing Professional Services , Maureen Broderick offers the solution. Broderick has brought together modern best practices for these and other crucial areas of professional services management: · Building, communicating, and maintaining shared vision, values, and culture · Recruiting, training, and evaluating people · Crafting the right strategies, portfolio, and mix of clients · Innovating and sharing knowledge · Financial planning, metrics, and reporting · Positioning: brand, marketing, and sales · Defining effective partnerships: equity, selection, and compensation · Ensuring responsibility and accountability · Organizational design, structure, governance, and systems · Leading effectively, and growing the next generation of leaders This book reflects Broderick & Co.'s unparalleled research into professional services management, including 200+ executive interviews with leaders and innovators in organizations of all sizes and types.